Statistical Assessment of two Rekeying Mechanisms applied to the Generation of Random Numbers - Peñate, Adrián Alfonso; Echevarria, Daymé Almeida; Argudín, Laura Castro (Journal of Science and Technology on Information security, 2021)
Abstract—The block ciphers modes of operation with internal rekeying mechanisms, used during the encryption of a message to increase their security, have been a subject of analysis in recent years. In this paper, we will analyze the randomness of the sequences generated by two of these modes of operation, which also will be used in the generation of pseudo-random numbers. Tóm tắt—Trong những năm qua, các chế độ mã hóa khối hoạt động với cơ chế tạo lại khóa bên trong, được sử dụng trong quá trình mã hóa tin nhắn đã trở thành đối tượng nghiên cứu trong những năm qua để tăng tính bảo mật. Trong bài báo này, chúng tôi sẽ phân tích tính ngẫu nhiên của chuỗi được tạo bởi hai trong số các chế độ này, mà cũng sẽ được sử dụng trong việc tạo ra các số giả ngẫu nhiên.